Differences in eating quality and electronic sense of meat samples as a function of goat breed and postmortem rigor state. (February 2022) - Li, Shaobo; Xiang, Can; Ge, Yue; Liu, Huan; Zhang, Dequan; Wang, Zhenyu
Graphical abstract: Highlights: Free moisture contents of pre-rigor goat meat samples were lower than those of rigor goat meat samples. Aromatic constituents contents of post-rigor goat meat samples were higher than those of pre-rigor goat meat samples. Sweet taste and bitterness of post-rigor goat meat samples were higher than those of pre-rigor goat meat samples. Abstract: Understanding the pre- and post-rigor meat quality characteristics is crucial for the development of featured goat meat products. To evaluate the quality characteristics of goat meat in different rigor states, knuckle muscle in pre-rigor, rigor, and post-rigor states of Taihang and Huanghuai goats were used to analyze chemical characteristics, water mobility, and electronic sense. Results indicated that Taihang and Huanghuai goat meat samples were rich in protein and essential amino acids, especially Lys. Pre-rigor goat meat samples had lower content of free moisture and higher water holding capacity than post-rigor goat meat samples. Furthermore, Taihang and Huanghuai goat meat samples exhibited different odour characteristics. Aromatic constituents content of post-rigor goat meat samples were greater than those of pre-rigor goat meat samples. The sweetness and bitterness of post-rigor goat meat samples were higher than those of pre-rigor goat meat samples. In conclusion, Taihang and Huanghuai goat meat samples have different quality characteristics, which were regulated by rigor state through different texture and flavor profiles.